Knowledge and attitudes of undergraduate nursing students toward dementia: An Indian perspective - Vijayalakshmi Poreddi; Brian D Carpenter; Sailaxmi Gandhi; Rama Chandra; Sailaxmi GandhiSuresh BadaMath (Universidad de Antioquia, 2015)
Objective.This work evaluated nursing students' knowledge and attitudes toward individuals with Alzheimer's disease and dementia. Methodology. This was a transversal, descriptive study carried out with a randomly selected group of nursing students (N = 122) from Bangalore, India, in 2013. The study used the Alzheimer's Disease Knowledge scale (30 questions with true-false options) and the Attitude toward Alzheimer's Disease and Related Dementias scale (20 questions scored with seven Likert-type options; the higher the score, the better the attitude). Results. The findings revealed that 56% of the questions were answered correctly and the average attitude score was 95 ± 1.5. A negative correlation was observed between age and knowledge of dementia (r = -0.323; p < 0.001). Conclusion. The participants have inadequate knowledge of dementia. However, they have positive attitudes towards patients with dementia, giving way to improving their knowledge related to this disease. Thereby, there is urgent need to enhance the undergraduate study plan with respect to the content of this theme and strengthen the attitudes of comprehensive care to individuals with dementia.